2020
DOI: 10.1136/bmjopen-2020-037904
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular accident and acute coronary syndrome and perioperative outcomes (CAPO) study protocol: a 10-year database linkage between Hospital Episode Statistics Admitted Patient Care, Myocardial Infarction National Audit Project and Office for National Statistics registries for time-dependent risk analysis of perioperative outcomes in English NHS hospitals

Abstract: IntroductionAn increasing number of people who have a history of acute coronary syndrome or cerebrovascular accident (termed cardiovascular events) are being considered for surgery. Up-to-date evidence of the impact of these prior events is needed to inform person-centred decision making. While perioperative risk for major adverse cardiac events immediately after a cardiovascular event is known to be elevated, the duration of time after the event for which the perioperative risk is increased is not clear.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Linking HES records to the Myocardial Infarction National Audit Project (MINAP), additional acute coronary syndrome cases were identified. Further details about the study design, cardiovascular events, and surgery codes can be found in the prospectively published protocol . Ethical approval was obtained from East Midlands – Nottingham research ethics committee and Health Research Authority confidential advisory group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking HES records to the Myocardial Infarction National Audit Project (MINAP), additional acute coronary syndrome cases were identified. Further details about the study design, cardiovascular events, and surgery codes can be found in the prospectively published protocol . Ethical approval was obtained from East Midlands – Nottingham research ethics committee and Health Research Authority confidential advisory group.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded cardiac surgery, neurosurgical, carotid endarterectomy, obstetrics, tracheostomy, and percutaneous gastrostomy. 16 Cardiac procedures were excluded based on a preexisting specialty-specific risk prediction tool (EuroSCORE II) and lack of specificity within ICD-10 coding making it impossible to reliably identify type III to V myocardial infarctions. Neurosurgery and carotid endarterectomy were excluded based on the recognized high stroke risk specific to these procedures.…”
Section: Meaningmentioning
confidence: 99%
“…Stroke, also known as cerebrovascular accident, shows high morbidity, high mortality, high disability, and high recurrence (Pan, 2018 ; D'Ancona et al, 2020 ). At present, the incidence of stroke exceeds that of tumors and heart diseases in China, and it has become the world's second and the China's first most fatal disease (Luney et al, 2020 ; Xia et al, 2021 ). Hemiplegia is the most common sequelae of stroke.…”
Section: Introductionmentioning
confidence: 99%